ICT in Enterprise Architecture of E-companies in Light of Studies on the Sector of Small and Medium Enterprises in Wielkopolska - Adamczewski, Piotr (Advanced Information Technologies for Management – AITM 2008, 2008)
An active sector of small and medium enterprises (SME) is a prerequisite of a properly functioning market economy. This sector encompasses various companies: those producing very simple goods and products as well as technologically advanced ones, which take advantage of the newest scientific achievements. A large part of these SMEs in Poland is having a very hard time competing with large companies. The multinationals have lower production costs, more points of sale, can spend more on advertising and operate on thinner profit margins. The ICT (Information and Communication Technology) can help even the odds. ERP (Enterprise Resource Planning) systems are more and more adopted in large companies. It appears that this trend is also being followed by small- and medium-sized companies. We have conducted a questionnaire-based survey to identify how Wielkopolska SMEs perceive this phenomenon of ICT and ERP systems.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 9-16